Evaluation of structural and functional changes in the myocardium in patients with acute myeloid leukemia during chemotherapeutic treatment - A. V. Chibashova; I. L. Davydkin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Cardiovascular toxicity is one of the most common complications of chemotherapeutic treatment. The most common method for diagnosing cardiovascular toxicity is to assess the structure and function of the left ventricle.The aim of the study was to investigate structural and functional changes in the myocardium of the left ventricle and left atrium in patients with acute myeloid leukemia during chemotherapeutic treatment.Materials and methods: the study included 110 patients with newly diagnosed acute myeloid leukemia who were prescribed polychemotherapy with anthracycline drugs. The parameters of the structure and function of the left ventricle were assessed based on transthoracic echocardiography using the specle-tracking technique and determination of the global longitudinal deformation of the left ventricle. Results. In patients with acute myeloid leukemia and verified cardiovascular toxicity, significant changes in the size (EDR, SSR) and volume of the left ventricle (EDV, ESV) were detected. Impaired systolic function was manifested by a decrease in the left ventricular ejection fraction and relative global longitudinal deformation, with a decrease in LV GLS preceding a decrease in LV EF. Diastolic dysfunction in patients with identified cardiovascular complications of anthracycline-containing polychemotherapy was manifested by a decrease in the E/A ratio, e' septal, e' lateral.Conclusions: In patients with acute myeloid leukemia receiving anthracycline-containing polychemotherapy, structural and functional changes in the left ventricular myocardium are detected, consisting in an increase in the size and volume of the left ventricle, as well as in the occurrence of systolic and diastolic dysfunction. A reliable sign of cardiovascular toxicity is a decrease in the global longitudinal deformation of the left ventricle.